Studi Pengaruh Suhu Penyimpanan terhadap Mutu Pisang Kepok (Musa paradisiaca formatypica) - Andi Nur Faidah Rahman; Victor Crystaline Muhammad; Februadi Bastian (jurnal1, 2021)
Kepok bananas are processed bananas that have ABB genotype, the letter B indicates that banana kepok has a stronger resistance to disease and chilling injury in cold temperatures storage. Storage at cold temperatures can extend the shelf life of bananas, because cold temperatures can slow down the respiration and enzymatic processes. The purpose of this study is to observe the effect of storage temperature on quality and shelf life, and to determine optimum storage temperature. The method used is storage temperature at room, 15oC and 10oC until the banana is damaged. The parameters observed were respiration patterns, weight loss, hardness, fruit skin color, total acid, vitamin C, pH, and total soluble solids. The results showed that bananas stored at cold temperatures (10oC and 15oC) can last up to 20 days while at room temperature only lasts for 10 days. Kepok bananas stored at 10oC have not shown symptoms of chilling injury.